AB0059 Chromatin Modifying Mechanisms in Macrophages Differ between Healthy Controls and Patients Wih Rheumatoid Arthritis. (10th June 2014) - Rooke, K.; Kruidenier, L.; Che, H.; Mander, P.; Swales, C.; Prinjha, R.; Oppermann, U.
Abstract : Background: Macrophages are central players in the pathogenesis of rheumatoid arthritis, and targeted inhibition of their principal cytokine products, TNFα and IL-6, are effective treatments. However, a significant proportion of patients still fail to respond to current therapies, and there is a continuing need for new therapeutic targets. Epigenetic modifications are increasingly recognised as key pathogenic features of RA and therefore inhibition of epigenetic anomalies has been identified as a potential future therapeutic strategy. Objectives: This study used small molecule inhibitors to identify epigenetic factors that mediate macrophage-derived pro-inflammatory cytokine production from healthy donors and patients with RA. Methods: Peripheral blood monocytes (PBMCs) were isolated from 10 healthy donors and 3 patients with rheumatoid arthritis; synovial fluid (SF) macrophages were also derived from the RA patients following therapeutic arthrocentesis. All patients were recruited from the Nuffield Orthopaedic Centre and gave written informed consent. PBMCs were differentiated into macrophages and stimulated with lipopolysaccharide (LPS) as a model of inflammation. PBMC and SF-derived macrophages were then treated with a panel of small molecule bromodomain, demethylase and deacetylase inhibitors to assess the impact of chromatin modification on macrophage pro-inflammatory cytokine production, including TNFα and IL-6. Cytokine production was detected by multiplex ELISA and supported by q-PCR data. Cell viability was determined using a WST-1 assay. Results: Macrophages from healthy volunteers and patients with RA responded differently to the tested epigenetic inhibitors. Bromodomain (PFI-1, (+)-JQ1 and I-BET), demethylase (GSK-J4) and deacetylase (SAHA and CXD101) inhibitors all significantly reduced the production of TNFα and IL-6 from healthy donor PBMC-derived macrophages. The bromodomain and demethylase inhibitors effectively inhibited cytokine production from the PBMCs of patients with RA, but of the deacetylase inhibitors tested, only SAHA had significant effect. In addition, cytokine production from RA SF-derived macrophages was significantly reduced by the bromodomain inhibitors and SAHA-mediated deacetylase inhibition, but there was no significant effect with demethylase inhibition. Conclusions: Differential responses to epigenetic inhibitors may represent differences in epigenetic modifications or mechanisms between healthy and RA macrophages. Further investigation into these differences, as well as specific mechanistic effects of epigenetic inhibitors, could lead to a clearer understanding of disease pathogenesis and help to identify novel therapeutic targets. Acknowledgements: This work was generously funded by BBSRC and GSK Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4218